Impact of Modern Communication Channels on Business Processes (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Business organizational communication, due to digitalization and transformations that take place in this sense in all business processes, takes a significantly different form from the one that used to be usually up to recently. Online business communication is usually more economical and faster than offline communication, and this reflects its important advantages, but the lack of contact can be one of the disadvantages and can lead to information overload and reduced concentration of recipients. The pandemic, which has driven businesses to focus on digital communication channels as much as possible, certainly has a significant impact on accelerating this change. Determining the extent to which these channels are optimal for overall business and communication processes is the focus of this paper, which presents secondary research of available scientific theory. The aim of this paper is to gather in one place the known scientific facts and determine in which future direction research of business communication should go. The paper shows the impact of the need to adapt to new communication channels on stress levels and points to the problem of a lack of feedback with nonverbal signals that are common in traditional contact communication (which is not online). In addition, the results indicate increased use of written business communication, which raises questions about the increased need for education in this regard.